Association between retirement behavior and financial goals: A comparison between urban and rural citizens in China - Chavis Ketkaew; Chutima Sukitprapanon; Phaninee Naruetharadhol (Cogent Business & Management, 2020)
This study compares the financial planning behavior of urban and rural citizens in China. Data from 399 urban citizens and 315 rural citizens were analyzed by applying the structural equation modeling (SEM) approach and the multi-group analysis (MGA) so that urban and rural citizens' retirement behaviors were able to compare. We found that an individual's retirement behavior is related to perceived retirement benefits, perceived health status, financial attainment capacity, and perceived parental burden. The SEM model also suggested the positive relationship between retirement behavior and individual short-term financial goals, which in turn influence long-term financial goals. Finally, the MGA indicated behavior differences between rural and urban citizens in terms of retirement benefit sufficiency and perceived parental burden.
Keywords: 650; retirement behavior; financial goals; urban and rural